Emitting area limitation via scattering control in phosphor film realizing high-luminance laser lighting. Issue 2 (February 2022) - Xu, Jian; Wang, Lanjie; Gu, Wen; Jiang, Zhi; Chen, Xinrong; Hu, Baofu; Du, Baoli; Ji, Haipeng; Dam-Hansen, Carsten; Jensen, Ole B.
Abstract: One major benefit of laser lighting is the possibility to achieve very high luminance. In phosphor-converted laser lighting systems, a blue (pump) laser can be focused into a very small spot. However, after excitation of the phosphor, the white-light-emitting area usually increases considerably, which reduces the luminance parameter substantially. Herein, we design and investigate a highly scattering YAG:Ce/glass composite film with a porous microstructure. Both the glass/phosphor interfaces and the introduced pores act as scattering centers, which can confine the emission area effectively. The relationship between the spot size and the microstructure (porosity, phosphor-particle size, thickness) is elucidated. Under excitation with blue laser, the composite film shows a uniform white-light emission with high luminous efficacy (230 lm/W) and high saturation threshold (> 40 W/mm 2 ), thus achieving a high luminous exitance of ∼1239 lm/mm 2 . With above excellent properties, the designed composite films show great potential for use in high-luminance laser lighting.